B-cell activating factor BAFF as a novel alert marker for the immunological risk stratification after kidney transplantation - Schuster, Antonia Margarete; Miesgang, N.; Steines, L.; Bach, Christian; Banas, B.; Bergler, T. (Immunologic Research, 2021)
The B cell activating factor BAFF has gained importance in the context of kidney transplantation due to its role in B cell survival. Studies have shown that BAFF correlates with an increased incidence of antibody-mediated rejection and the development of donor-specific antibodies. In this study, we analyzed a defined cohort of kidney transplant recipients who were treated with standardized immunosuppressive regimens according to their immunological risk profile. The aim was to add BAFF as an awareness marker in the course after transplantation to consider patient’s individual immunological risk profile. Included patients were transplanted between 2016 and 2018. Baseline data, graft function, the occurrence of rejection episodes, signs of microvascular infiltration, and DSA kinetics were recorded over 3 years. BAFF levels were determined 14 d, 3 and 12 months post transplantation. Although no difference in graft function could be observed, medium-risk patients showed a clear dynamic in their BAFF levels with low levels shortly after transplantation and an increase in values of 123% over the course of 1 year. Patients with high BAFF values were more susceptible to rejection, especially antibody-mediated rejection and displayed intensified microvascular inflammation; the combination of high BAFF + DSA puts patients at risk. The changing BAFF kinetics of the medium risk group as well as the increased occurrence of rejections at high BAFF values enables BAFF to be seen as an awareness factor. To compensate the changing immunological risk, a switch from a weaker induction therapy to an intensified maintenance therapy is required.
CRIS-Team Scopus Importer:2021-08-20
Keywords: ABMR; BAFF; Immunological risk stratification; Kidney transplantation